Edukasi Bijak Dalam memilih Makanan di Aplikasi Pesan Antar pada Masa New Normal - Ratna Hamidah; Ratih Kurniasari; Linda Riski Sefrina; Sabrina Sabrina (Abdimas Universal, 2022)
The fast-spreading Corona virus requires the government to take policies quickly to break the chain of its spread. Various ways are done starting from diverting all activities that are usually done offline to online. This increase in the use of technology is due to activity restrictions and causes people to spend more time at home, one of which is buying food online through delivery applications, resulting in many people choosing food without paying attention to the nutritional content contained in the food. Nutritional problems in adults tend to lead to obesity. One of the factors that influence nutritional status is nutritional knowledge. One of the prevention efforts that can be done is through education to increase public knowledge. This education is carried out online with the theme "Education Wisely in Choosing Food in the Delivery Application During the New Normal" with pocket books and Instagram social media accounts. This activity begins with a pretest and ends with a posttest to assess the increase in knowledge. There was an increase in the value of the results of the pretest and posttest scores as well as pocket book media and Instagram social media accounts which affected the increase in respondents' knowledge. Respondents of this activity have normal nutritional status as many as 35 respondents out of 60 respondents.